Evaluating the Effectiveness of Holistic Integrative Early Childhood Education Policy Implementation in Indonesia - Murtoko, Murtoko; Amalia, Nur Fadlilah; Saputra, Gilang Bangkit (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
This study evaluates the effectiveness of Holistic Integrative Early Childhood Education (HIECE) policy implementation in Kulon Progo Regency, Indonesia. Guided by a descriptive quantitative design, the research involved 100 Early Childhood Education (ECE) institutions formally trained in HIECE service delivery. Data were collected using a structured questionnaire based on five core service domains: educational services; nutrition, health, and care; childcare; protection; and welfare. Results indicate an overall moderate effectiveness, with welfare services scoring highest (3.25), followed by education (3.14), health and care (3.13), childcare (2.49), and protection (2.13). While most institutions demonstrated competence in educational and health-related services, significant weaknesses were found in parental engagement and welfare support, including access to civil documentation and health insurance. The findings highlight the critical role of cross-sector collaboration, community involvement, and institutional capacity in policy realization. This study contributes empirical insights to inform localized strategies for strengthening early childhood systems and advancing child well-being through integrative, inclusive, and context-sensitive approaches.